Development and evaluation of a continuous microwave processing system for hydrocarbon removal from solids - Buttress, A.J.; Binner, E.; Yi, C.; Palade, Paula; Robinson, J.; Kingman, S.W. (Elsevier, 2016)
A continuous conveyor-belt processing concept using microwave heating was developed and evaluated. Four hydrocarbon-contaminated soils were used as model feedstocks, and the degree of organic removal was assessed against the power and energy input to the process. The findings of this study at scale (150kg/h) are in direct agreement with data obtained in batch laboratory scale experiments, and show that microwave heating processes are fundamentally scalable. It is shown that there is a trade-off between the efficiency of organic removal and the power distribution, and applying the power in a single stage was found to be 20-30% more energy efficient but the overall degree of organic removal is limited to 60%. 75% removal was possible using two processing steps in series, but the organic removal is ultimately limited by the amount of power that can be safely and reliably delivered to the process material. The concept presented in this work is feasible when 75% organic removal is sufficient, and could form a viable industrial-scale process based on the findings of this study.